2007
DOI: 10.1208/pt0802046
|View full text |Cite
|
Sign up to set email alerts
|

Taste masking of ondansetron hydrochloride by polymer carrier system and formulation of rapid-disintegrating tablets

Abstract: The purpose of this research was to mask the intensely bitter taste of ondansetron HCl and to formulate a rapiddisintegrating tablet (RDT) of the taste-masked drug. Taste masking was done by complexing ondansetron HCl with aminoalkyl methacrylate copolymer (Eudragit EPO) in different ratios by the precipitation method. Drug-polymer complexes (DPCs) were tested for drug content, in vitro taste in simulated salivary fluid (SSF) of pH 6.2, and molecular property. Complex that did not release drug in SSF was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 18 publications
5
74
0
2
Order By: Relevance
“…The diffractograms of bromocriptine mesylate as a pure drug and the selected formula were obtained. The study was confirmed by using Shimadzu XRD-6000 powder X-ray diffractometer at continuous scan range of 5 °-80 ° of 2Ɵ The operating voltage was 40 (kV) and current 30mA [24].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 99%
“…The diffractograms of bromocriptine mesylate as a pure drug and the selected formula were obtained. The study was confirmed by using Shimadzu XRD-6000 powder X-ray diffractometer at continuous scan range of 5 °-80 ° of 2Ɵ The operating voltage was 40 (kV) and current 30mA [24].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 99%
“…The optimized ratio of 1:3 CTZ:hydroxypropyl β-CD was appropriate for taste masking [9,10] . CTZ was coated by a fluidized bed coating using Eudragit ® RL30-D and taste-masking evaluation was performed by healthy human volunteers and their perceived levels were recorded on a numerical scale [11,12] . Moreover, rizatriptan benzoate and β-CD prepared by kneading with distilled water demonstrated effective taste masking [13] .…”
Section: Research Papermentioning
confidence: 99%
“…In vitro disintegration study [19][20][21] The in vitro disintegration test for prepared tablets was carried out using USP disintegration test apparatus. Six tablets were placed individually in each tube of disintegration test apparatus, and discs were placed over each tablet.…”
Section: Content Uniformity Test [18]mentioning
confidence: 99%